Televised Cartoons and Incidental Learning of Foreign Language among Children: A Case Study of Doraemon Cartoon in Pakistan: Doraemon Cartoon in Pakistanakht Rawan, Mahwish Dar, Syed Abdul Siraj (PJDOL, 2023)
Learning once deemed as a face-to-face/classroom activity has been revolutionized by the advent of new information and communication technologies (ICTs). These technologies are used for the new modes of education such as distance education, virtual learning, e-learning and online learning.This study examines that whether children’s exposure to television cartoon results into incidental learning regarding different cultural elements, especially language.